Environmental Sustainability Analysis based on a Physical Model - Gonzales Torres, Mario (2019)
The research analyzes the sustainability of environmental indicators, which is essential in the proposals for sustainable development models. In similarity to the ideal physical model of the harmonic movement of masses for its application in a sustainability concept, the Adapted Holzer Method is used to conceptualize the Sustainable Harmonic Movement (MAS) in its economic, social, environmental and institutional dimensions of the system components environmental. The main characteristics, advantages and disadvantages of MAS are exposed. Likewise, the requirements and the analysis of graphics are established for the acceptance of simulations of the models. Finally, the sustainability simulation results applied to a group of environmental indicators are presented. The application verifies that the analysis of sustainability components using the physical model facilitates decision-making to opt for an optimal model of indicator values.